4.6k views
0 votes
Solve the following equation for x (linear equation):


(b-cx)/(a) + (a-cx)/(b) + 2 = 0

User Kota
by
5.0k points

1 Answer

8 votes

Answer:


\displaystyle x=(a+b)/(c)

Explanation:

Equations

Solve the equation:


\displaystyle (b-cx)/(a)+(a-cx)/(b)+2=0

Subtracting 2:


\displaystyle (b-cx)/(a)+(a-cx)/(b)=-2

Multiply by ab to eliminate denominators:


\displaystyle ab(b-cx)/(a)+ab(a-cx)/(b)=-2ab

Simplifying:


b(b-cx)+a(a-cx)=-2ab

Operating:


b^2-bcx+a^2-acx=-2ab

Subtracting
b^2+a^2


-bcx-acx=-2ab-b^2-a^2

Multiplying by -1:


bcx+acx=2ab+b^2+a^2

Factoring:


c(b+a)x=2ab-b^2+a^2

The right side of the equation is the square of a+b:


c(b+a)x=(a+b)^2

Simplifying (for a ≠ -b):


cx=(a+b)

Dividing by c:


\boxed{\displaystyle x=(a+b)/(c)}

User AlekseyS
by
5.1k points